Application of bioactive glycolipids to control Listeria monocytogenes biofilms and as post-lethality contaminants in milk and cheese. (May 2021) - Sun, Lang; Forauer, Emily C.; Brown, Stephanie R.B.; D'Amico, Dennis J.
Abstract: Listeria monocytogenes can form persistent biofilms on food processing surfaces, resulting in cross-contamination of food products, including milk and milk products. Natural glycolipids are a promising intervention to control undesirable microbes due to their antimicrobial activity and low toxicity. This study aimed to determine the antimicrobial activity of glycolipids to control L. monocytogenes biofilms as well as in milk and on Queso Fresco. Application of a natural glycolipid product significantly reduced biofilm-associated L. monocytogenes on both polystyrene and stainless steel at concentrations as low as 45 mg/L. When added to UHT skim milk, a concentration of 1000 mg/L inhibited L. monocytogenes growth through 7 days of storage at 7 °C, and application of 1300 and 1500 mg/L reduced counts to levels below the limit of enumeration at day 21. In contrast, 2000 mg/L were necessary to inhibit growth through 7 days in whole milk. Glycolipid solutions at concentrations ≥10% reduced L. monocytogenes counts on Queso Fresco through 7 days when applied as a dip. Overall, natural glycolipids have potential as a natural alternative for the removal of biofilms and as an antimicrobial to control L. monocytogenes in milk and milk products with short shelf lives. Highlights: Glycolipids were inhibitory and bactericidal at low concentrations in growth media. Novel glycolipid product inactivated biofilm-associated L. monocytogenes. Subinhibitory concentrations of novel glycolipid did not inhibit biofilm formation. Bactericidal activity of novel glycolipid was higher in skim than whole milk. Novel glycolipid inhibited early L. monocytogenes growth on Queso Fresco.